ANALISIS DAMPAK IMPLEMENTASI STANDAR PENJAMINAN MUTU TERHADAP PENINGKATAN KUALITAS PENDIDIKAN DI MADRASAH IBTIDAIYAH TERPADU BINA INSAN RABBANI: AN ANALYSIS OF THE IMPACT OF THE IMPLEMENTATION OF QUALITY ASSURANCE STANDARDS ON IMPROVING THE QUALITY OF EDUCATION IN THE INTEGRATED MADRASAH IBTIDAIYAH BINA INSAN RABBANI. - Aman, Aman; Yulianti, Nuri; Handayani, Winarni; Nazar, Muhammad (Perkumpulan Peneliti dan Pegiat Literasi, 2025)
Education quality assurance is one of the important instruments in realizing quality and sustainable education. This study aims to determine and analyze the impact of the implementation of quality assurance standards on improving the quality of education at MI Terpadu Bina Insan Rabbani. The approach used is qualitative with a case study method. Data collection techniques were conducted through observation, in-depth interviews, and documentation. The results showed that the implementation of quality assurance standards has had a positive impact on several important aspects, such as increased teacher competence, learning effectiveness, more organized school management, and parental satisfaction with education services. However, there are still some obstacles in the implementation, such as limited human resources, high administrative burden and the need for continuous training for all school elements. This study recommends the need to strengthen internal supervision programs, increase the capacity of teachers and education personnel, and integrate the quality assurance system into the overall school work culture so that the quality of education can be continuously improved.